Analysing Sound Environment and Architectural Characteristics of Libraries through Indoor Soundscape Framework - DOKMECI YORUKOGLU, Papatya Nur; KANG, Jian (Archives of Acoustics, 2016)
This study presents the indoor soundscape framework in detail by describing the variables and factors that form an indoor soundscape study. The main objective is to introduce a new indoor soundscaping framework and systematically explain the variables that contribute to the overall evaluation of an indoor soundscape. Hence, the dependencies of physical and psychoacoustical factors of the sound environment and the spatial factors of the built entity are statistically tested. The new indoor soundscaping framework leads to an overarching evaluation perspective of enclosed sound environments, combining objective room acoustics research and noise control engineering with architectural analysis. Therefore, it is hypothesised that case spaces with certain plan organisations, volumetric relations, and spatial referencing lead to differentiated sound pressure level (SPL) and loudness (N) values. SPL and N parametric variances of the sound environments are discussed through the statistical findings with respect to the architectural characteristics of each library case space. The results show that the relation between crowd level variances and sound environment parametric values is statistically significant. It is also found that increasing the atrium height and atrium void volume, the atrium’s presence as a common architectural element, and its interpenetrating reference and domain containment results in unwanted variances and acoustic formations, leading to high SPL and N values.